Ladybird read with me: the space boat (key words reading scheme) - Murray, William; Corby, Jill Davis, Jon (Ladybird Books London, 2011)
A fun reading scheme that uses the 'look and say' approach to learning to read. Essential key words are introduced and regularly repeated to assist with pronunciation and meaning. Level two is for the developing reader.